2016
DOI: 10.1002/jbm.a.35862
|View full text |Cite
|
Sign up to set email alerts
|

Novel porous poly(propylene fumarate‐co‐caprolactone) scaffolds fabricated by thermally induced phase separation

Abstract: Scaffolds with porous structures are highly applicable for tissue engineering and regenerative medicine. In the present study, 3-dimensional poly(propylene fumarate-co-caprolactone) [P(PF-co-CL)] scaffolds were fabricated from a P(PF-co-CL)-dioxane-water ternary system through thermally induced phase separation (TIPS). Cloud points of P(PF-co-CL) in dioxane-water solutions increased with increased solute concentration, but increased dioxane composition decreased cloud point. Among 3 polymer concentrations (4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Highly porous scaffolds can be prepared through the TIPS procedure, which is critical for tissue regeneration. , Though no consensus regarding the certain porosity values, ideal pore size, and percentage of interconnected pores has been made, previous reports confirmed that high porosity values are advantageous for tissue regeneration. The present study revealed that the scaffold prepared through the TIPS procedure not only supports adhesion and proliferation of RBMSCs but also facilitates their immigration.…”
Section: Discussionmentioning
confidence: 99%
“…Highly porous scaffolds can be prepared through the TIPS procedure, which is critical for tissue regeneration. , Though no consensus regarding the certain porosity values, ideal pore size, and percentage of interconnected pores has been made, previous reports confirmed that high porosity values are advantageous for tissue regeneration. The present study revealed that the scaffold prepared through the TIPS procedure not only supports adhesion and proliferation of RBMSCs but also facilitates their immigration.…”
Section: Discussionmentioning
confidence: 99%
“…22 The technical principles of using TIPS to fabricate interconnected scaffolds were previously described, 20 and the dioxane-water binary solvent was developed in an earlier study for inducing phase separation in a homogenized solvent. 36 However, different polymers have their own properties, which influence solubility in different solvent systems and phase separation processes. In the present work, we explored the effects of various PPF-co-PLGA concentrations and dioxane-water ratios on the 3D structures and characteristics of scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al reported that the concentration of PPF and solvents ratio strongly affected the formation of pores into the structure of scaffold. They mentioned that among different concentrations of (4, 8, and 12 wt%) polymer, 8 wt% demonstrated the best pore interconnectivity for nerve tissue engineering applications [118].…”
Section: Pcl Polymermentioning
confidence: 99%